Understanding client satisfaction with a health insurance scheme in Nigeria: factors and enrollees experiences - Sambo Mohammad N; Mohammed Shafiu; Dong Hengjin (BMC, 2011)
Abstract Background Health insurance schemes have been widely introduced during this last decade in many African countries, which have strived for improvements in health service provision and the promotion of health care utilization. Client satisfaction with health service provision during the implementation of health insurance schemes has often been neglected since numerous activities take place concurrently. The satisfaction of enrollees and its influencing factors have been providing evidence which have assisted in policy and decision making. Our objective is to determine the enrollee's satisfaction with health service provision under a health insurance scheme and the factors which influence the satisfaction. Methods This retrospective, cross-sectional survey took place between May and September 2008. Two hundred and eighty (280) enrollees insured for more than one year in Zaria-Nigeria were recruited using two stage sampling. Enrollee's satisfaction was categorized into more satisfied and less satisfied based on positive responses obtained. Satisfaction, general knowledge and awareness of contribution were each aggregated and assessed as composite measure. Logistic regression analysis was used to analyze factors that influenced the satisfaction of enrollees. Results A high satisfaction rate with the health insurance scheme was observed (42.1%). Marital status (p < .05), general knowledge (p < .001) and awareness of contributions (p < .05) positively influenced clients' satisfaction. Length of employment, salary income, hospital visits and duration of enrolment slightly influenced satisfaction. Conclusions This study highlighted the potential effects of general health insurance knowledge and awareness of contributions by end-users (beneficiaries) of such new program on client satisfaction which have significant importance. The findings provided evidence which have assisted the amendment and re-prioritization of the medium term strategic plan of operations for the scheme. Future planning efforts could consider the client satisfaction and the factors which influenced it regularly.